2011
DOI: 10.1111/j.1365-2966.2011.18637.x
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime measurements and calculations in Y+ and Y2+ ions

Abstract: We report a new set oftheoretical transition probabilities in Y II, obtained using a multiconfiguration relativistic Hartree-Fock method including core polarization. The overall quality of the calculations is assessed by comparisons with new and previous lifetime measurements. In this paper, we report new measurements of five lifetimes in the 4d5p and 5s5p configurations, in the energy range of 32 048-44 569 cm −1 , obtained by the time-resolved laser-induced fluorescence method. A similar theoretical model, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 26 publications
3
49
1
Order By: Relevance
“…Although the pair correlation (PC) terms are not as strong as CP, they are significant for precise calculations and are included in our present RCC formalism. Biémont et al [15] used core polarization correction as a modification of the relativistic Hartree-Fock method (HFR+CPOL) to calculate the oscillator strengths of various transitions of Y III. The all-order relativistic many-body perturbation theory (RMBPT) used by Safronova and Safronova [14], employs correlation operators associated with single and double excitations, but with a linearized approximation.…”
Section: Resultsmentioning
confidence: 99%
“…Although the pair correlation (PC) terms are not as strong as CP, they are significant for precise calculations and are included in our present RCC formalism. Biémont et al [15] used core polarization correction as a modification of the relativistic Hartree-Fock method (HFR+CPOL) to calculate the oscillator strengths of various transitions of Y III. The all-order relativistic many-body perturbation theory (RMBPT) used by Safronova and Safronova [14], employs correlation operators associated with single and double excitations, but with a linearized approximation.…”
Section: Resultsmentioning
confidence: 99%
“…References are MA60 for Martin (1960), DR2006 for Drake (2006), NS81 for Nussbaumer & Storey (1981), KZ91 for Butler, K. & Zeippen, C. J. (1991), W96 for Wiese et al (1996), HBGV91 for Hibbert et al (1991), Si98 for Siegel et al (1998), K79 for Kaufman & Hagan (1979), H99 for Hannaford (1999), Ma01 for Matheron et al (2001), Sh61 for Shenstone (1961), LD89 for Lawler & Dakin (1989), FMW for Fuhr et al (1988), PTP for Pickering et al (2002), SN14 for Sansonetti & Nave (2014), NJ13 for Nave & Johansson (2013), T89 for Theodosiou (1989), RU98 for Raassen & Uylings (1998), PBL95 for Pinnington et al (1995), NBS for Miles & Wiese (1969), KO83 for Kostyk & Orlova (1983), Bie11 for Biémont et al (2011),L06 for Ljung et al (2006), MCS75 for Meggers et al (1975), BL48 for Biermann & Lübeck (1948), Bal81 for Biemont et al (1981), KL01 for Kling et al (2001), DSVD92 for Davidson et al (1992), SR01 for Sansonetti & Reader (2001), Do03 for Dolk et al (2003)…”
Section: Discussionmentioning
confidence: 99%
“…The star-to-star scatter is rel- (Sneden 1973). Using the transition probabilities of Hannaford et al (1982) and Biémont et al (2011), we used ten Y ii lines to derive For Star 2, we display our synthetic/observed spectrum match in Fig. 7.…”
Section: Neutron-capture Elementsmentioning
confidence: 99%